Large US bank takeovers in 2008: performance and implications. Issue 1 (26th October 2021) - Song, Guoxiang
Abstract : Purpose: Because systemically important banks' takeovers in the US were expected to contain the 2008 global financial crisis (GFC) but were found to have imposed large cost on shareholders, this paper examines the effectiveness of these acquisitions during the GFC and investigates what went wrong with the market for corporate control of large banks. Design/methodology/approach: This paper presents a model of the disciplinary takeover based on the efficient market hypothesis which provides appropriate measures for it to examine the financial performance of acquiring banks after takeover. Findings: The results indicate that the takeover market for large banks was ineffective in two aspects: the market did not distinguish strong banks from weak banks before the crisis and acquirers performed worse after takeover. Such ineffectiveness reflects the fundamental deficiencies of large bank takeovers arising from some key distinguishing characteristics of large banks. Research limitations/implications: The sample size of systemically important banks' takeovers is small so large-sample standard statistical inferences cannot be used. Practical implications: The deficiencies of large bank takeovers need to be rectified in order to aid in resolving future crises. Originality/value: This paper provides rare and detailed insight based on case studies of large US bank takeovers during the GFC.